Analisa Dampak Negatif Bermain Games Online Bagi Anak Pada Madrasah Ibtidaiyah Darul Hikmah - Etika Sabariah; Musthafa Kamil; Tri Indah Estiani; Dorit Hartini (CV. ITTC INDONESIA, 2023)
Development Technology in other form application include games online is still favorite for the children. Madrasah Ibtidaiyah (MI) Darul Hikmah is elementary school, that place Kecamatan Cinere Depok Jawa Barat. The problem having the theacher is the children become lazy study because addicted game onlines. So what the happens this became is implementation community service is guide the children limit play game online and divert the other playing with aplikasi PAINT microsof office and googel Lens. Result activity community service success and greeted enthusiastically from the children. Tree Tim from each prodi complete each other on direct the children limit play game online and divert the other playing with aplikasi PAINT microsof office and googel Lens